Drug metabolism in early infancy: opioids as an illustration. (4th March 2018) - Van Donge, Tamara; Mian, Paola; Tibboel, Dick; Van Den Anker, John; Allegaert, Karel
ABSTRACT: Introduction : Drug dosing in infants frequently depends on body weight as a crude indicator for maturation. Fentanyl (metabolized by Cytochrome P450 3A4) and morphine (glucuronidated by UDP-glucuronosyltransferase-2B7) served as model drugs to provide insight in maturation patterns of these enzymes and provide understanding of the impact of non-maturational factors to optimize dosing in infants. Areas covered : Systematic searches on metabolism and population pharmacokinetic (Pop-PK) models for fentanyl and morphine were performed. Pre- and post-model selection criteria were applied to assess and evaluate the validity of these models. It was observed that maturational changes have been rather well investigated, be it with variability in the maturational function estimates. The same holds true for Pop-PK models, where non-maturational covariates have also been reported (pharmacogenetics, disease state or external influences), although less incorporated in the PK models and with limited knowledge on mechanisms involved. Expert opinion : PK models for fentanyl and morphine are currently available. Consequently, we suggest that researchers should not continue to develop new models, but should investigate whether collected data fit in already existing models and provide additional value concerning the impact of (non)-maturational factors like drug-drug interactions or pharmacogenetics.